The acute effect of whole body vibration on the h-reflex recruitment curve in soleus muscle - Leila Dadashi; Giti Torkaman (Vesnu Publications, 2013)
Introduction: Despite the facilitatory effects after applied whole body vibration (WBV), results of some studies have shown the increase of muscle response depression. The purpose of this study was to investigate the acute response of H-reflex recruitment curve in soleus muscle after one session of WBV. Materials and Methods: Twenty six non-athletes volunteer healthy women (mean age ± SD; 26.11 ± 2.85 years) were participated in this study. All subjects received two different sham and test sessions. They stood on the vibration plate in semi squat position. In test session, WBV was applied with frequency of 30Hz and peak to peak amplitude of 3mm during 3 minutes. Soleus H-reflex recruitment curve was recorded before, immediately after, 5 and 10 minutes after WBV. Results: The intensity of H-reflex recruitment curve threshold and Hmax were significantly increased immediately after WBV in both sessions (P < 0.05). Peak to peak amplitude of initial H-reflex were prominently decreased in both sessions whereas, peak to peak amplitude of Hmax was decreased only in sham session (P < 0.05). The analysis of threshold and peak to peak amplitude, the parameters of H-reflex recruitment curve, between two sessions showed no significant difference (P > 0.05). Conclusion: Considering the right shift of H-reflex recruitment curve and depression response in two sham and test sessions, it seems that maintaining of semi squat position and activated control mechanisms, such as extensor muscles contraction, affects this inhibitory response and WBV had no facilitatory effect on this depression response. Keywords: H-reflex, Soleus muscle, Whole body vibration, Semi squat position